2011
DOI: 10.1209/0295-5075/96/40013
|View full text |Cite
|
Sign up to set email alerts
|

Universal amplitudes of the Casimir-like interactions between four types of rods in fluid membranes

Abstract: The fluctuation-induced, Casimir-like interaction between two parallel rods of length L adsorbed on a fluid membrane is calculated analytically at short separations d L. The rods are modeled as constraints imposed on the membrane curvature along a straight line. This allows to define four types of rods, according to whether the membrane can twist along the rod and/or curve across it. For stiff constraints, all the interaction potentials between the different types of rods are attractive and proportional to L/d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…It was ignored in the present work since it is normally sub-dominant for small inclusions imposing large membrane deformations. This Casimir force is known however to induce an effective attraction between long straight rods [52,53]. We have investigated straight rods in our simulations, and found that the latter have too weak Casimir interactions to induce rod clusters for the present length (N sg = 10).…”
Section: Summary and Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…It was ignored in the present work since it is normally sub-dominant for small inclusions imposing large membrane deformations. This Casimir force is known however to induce an effective attraction between long straight rods [52,53]. We have investigated straight rods in our simulations, and found that the latter have too weak Casimir interactions to induce rod clusters for the present length (N sg = 10).…”
Section: Summary and Discussionmentioning
confidence: 84%
“…We have exhibited the leading order term ∝ 1/R 2 , which describes the interaction quantitatively well for R larger than a few times r rod . Note that this interaction is of longer range than the ∝ 1/R 4 fluctuation-induced Casimir interaction between straight rods and it has a different angular dependence [52,53]. Graphs of this interaction are represented in Fig.…”
Section: Tensionless Membranementioning
confidence: 99%
“…This approximation was used in the case of disk-shaped inclusions in Refs. [37,58], showing that the fluctuation-induced interaction potential then scales as 1/d 1/2 . In Ref.…”
Section: Close Parallel Rodsmentioning
confidence: 98%
“…In addition, the interaction energy was studied numerically versus d/L, thanks to a discretization scheme [59], showing the transition between the asymptotic behaviors at large d/L [27] and at small d/L [58] were recovered. Finally, the bending and coming into contact of the rods due to the fluctuation-induced interaction was discussed: it was predicted to occur below a certain value of d [58].…”
Section: Close Parallel Rodsmentioning
confidence: 99%
See 1 more Smart Citation